Control of a Mycoplasma pneumoniae Outbreak in an Institutional Setting Using Azithromycin Prophylaxis - Gdalevich, Michael; Haas, Eric J.; Dukhan, Larisa; Katz, Manuel; Zelenski, Victoria; Moran-Gilad, Jacob (Frontiers in Public Health, 2018)
BaBackground: Mycoplasma pneumoniae is a major cause of respiratory infection of varying severity. Outbreaks of M. pneumoniae infection commonly occur in closed or semi-closed communities and settings. The control of such outbreaks is challenging, owing to delayed detection, long incubation period and paucity of infection control guidelines. Methods: Between May and July 2015, a residential facility for adults with developmental disabilities in Southern Israel witnessed an outbreak of acute respiratory infection, subsequently diagnosed as associated with M. pneumoniae. All relevant data were collected as a part of a formal outbreak investigation. Strict infection control procedures were implemented, and azithromycin prophylaxis was provided to all residents. Results: Out of 215 residents, there were 29 suspected cases, 23 of which were confirmed as M. pneumoniae infection by serology or nucleic acid testing, for an attack rate of 11%. There were no cases of severe or fatal illness. An infection control strategy including implementation of strict case isolation, enforcement of hygiene measures, a high index of suspicion for case detection, and use of azithromycin prophylaxis for all residents, led to rapid cessation of the outbreak. Discussion: The use of azithromycin prophylaxis may be worthwhile in closed institutional settings in which M. pneumoniae infections are documented. The dynamics of this outbreak suggest that if spread between wards is anticipated, expanding prophylaxis beyond immediate contacts of affected individuals should be considered.